Análisis del impacto ambiental de diferentes tipos de paneles solares según los materiales utilizados y los componentes tóxicos generados (2017)
The present monograph had several phases, where in the first of these was the identification of the processes involved in the construction of the Silicon and Cd-Te solar panels, besides giving a description of each of these stages for both types of panels already mentioned, in the second part an inventory was made based on the methodology of the life cycle of the Colombian technical standard ISO 14040, for each process where the materials, components used and emissions produced for each process were identified, in In this same phase, the outputs of emissions for each process were compared, comparing them among them, making an inventory with all the inputs and outputs of each stage already mentioned, determining the processes with the greatest negative impacts for the environment.